"You phubbed me for that?" Reason given for phubbing and perceptions of interactional quality and exclusion. Issue 3 (3rd March 2021) - McDaniel, Brandon T.; Wesselmann, Eric
Abstract: When someone focuses on their phone, rather than the person in front of them ("phubbing" or "technoference"), this can lead to feelings of exclusion and dissatisfaction. Few studies have examined this phenomenon experimentally using a confederate during face‐to‐face interactions, and to our knowledge the published research has yet to examine the role that attributional information may have on the effects of being phubbed. Thus, we conducted an experiment investigating how attributional information influenced the effects of phone use on feelings of exclusion and interactional quality during a face‐to‐face interaction. We randomly assigned 99 young adults into one of three conditions: no phone use, important use, or trivial use. In the phone conditions, the participant's interaction partner (a confederate) pulled out their phone 2 min into the interaction, gave either an important or trivial reason for use, and then interacted with their phone, making intermittent eye contact while continuing to interact with the participant. Phubbed individuals reported feeling more excluded, less close, and like the partner was more distracted in the phone use conditions, regardless of reason. However, individuals phubbed for an important reason reported feeling less excluded and like the partner was less distracted as compared with participants in the trivial condition. Results suggest that people take attributional information into account during the phubbing experience. Given the frequency of phone use during social interactions, these data suggest giving a good reason for use may help in relationships and interactions; yet, it may not alleviate all the potential negative effects.